Tradition Upgraded, ICH Redefined Through Innovation:: The Case of a Kun Qu Opera Costume Redesigned Embedding Kinetic Functionalitie - Parati, Ivan (Mimesis Journal, 2024)
The article presents the process behind redesigning a traditional costume of Chinese Kunqu opera, an innovation drawing on an unusual joint effort among digital and traditional manufacturing techniques and meant to revive the interest of a younger audience in traditional cultural heritage. The objective is to spark dialogue and collaboration among traditional crafts and contemporary manufacturing disciplines while generating an innovative esthetic and appealing narrative that younger generations may appreciate and support. The development of a postgraduate module at XJTLU Design School, sharing the same research project objective, supported the redesign process. Collaborating with a costume designer preserving a centuries-old crafting tradition was central to finalizing an initial prototype and planning further project development.